2009
DOI: 10.1007/s11426-010-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and transformation of cadmium by Phaeodactylum tricornutum

Abstract: In this paper, we report the bioaccumulation and transformation of cadmium (Cd) by Phaeodactylum tricornutum in the presence of ethylenediamine tetra acetic acid (EDTA) and cysteine (Cys). Both EDTA and Cys can alleviate the toxicity of Cd to P. tricornutum. Short term intracellular uptake and extracellular adsorption experiments using ICP-MS indicated that the amounts of Cd accumulated on the cell surface of P. tricornutum and inside the cell decreased along with the increase of EDTA concentration, which conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This was in accordance with the results observed in the cytotoxicity studies. Moreover, it should be noted that the uptake of Cd by P. tricornutum cells in the case of CdCl 2 exposure was the lowest compared with those of the CdTe-NPs, suggesting that P. tricornutum take up Cd 2+ and CdTe-NPs in different ways, in which that Cd 2+ is taken up via regulation of the ion-channels on the cell membrane 23 while CdTe-NPs are more easily taken up via cell endocytosis and release of Cd 2+ inside the cells thus causing damage.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This was in accordance with the results observed in the cytotoxicity studies. Moreover, it should be noted that the uptake of Cd by P. tricornutum cells in the case of CdCl 2 exposure was the lowest compared with those of the CdTe-NPs, suggesting that P. tricornutum take up Cd 2+ and CdTe-NPs in different ways, in which that Cd 2+ is taken up via regulation of the ion-channels on the cell membrane 23 while CdTe-NPs are more easily taken up via cell endocytosis and release of Cd 2+ inside the cells thus causing damage.…”
Section: Resultsmentioning
confidence: 95%
“…Representing one of two major classes of diatoms, P. tricornutum is the most widely utilized as a model for studying the ecology, physiology, biochemistry and molecular biology of diatoms. 20,21 The tolerance of P. tricornutum to Cd 2+ has been studied, 22,23 and the results obtained suggest that P. tricornutum has a detoxifying mechanism for chelating Cd 2+ by in vivo synthesized phytochelatins (PCs) and proteins similar to that of higher plants. [24][25][26] However, the cytotoxicity of CdTe-NPs to this typical diatom has not been reported.…”
Section: Resultsmentioning
confidence: 99%
“… Comparison of the EC 50 values (mg/L) of Phaeodactylum tricornutum from other studies to the present study: ( a ) the EC 50 values of potassium dichromate at 72 h; ( b ) the Cu values at 72 h; ( c ) the Cd values at 72 h [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. …”
Section: Figurementioning
confidence: 76%
“…Some authors reported that, at 72 h, the Cd EC 50 value for P. tricornutum was as high as 22.39 mg/L, which reveals its excellent tolerance to Cd. Compared with other microalgae species, they reported lower EC 50 values: 1.87 µg/L of Cd for Scenedesmus quadricauda , 2.13 µg/L for Aulacoseira granulate , and 1.8 mg/L for Teraselmis gracilis [ 60 , 61 ]. According to our results, EC 50 for Cd(NO 3 ) 2 was far-removed from the reference values of the aforementioned papers.…”
Section: Discussionmentioning
confidence: 99%
“…27 Under the flow injection mode, the reduction efficiencies of GSSG, vasopressin and insulin before and after UV-Ag/TiO 2 -HCOOH reduction with 1,4,7,10-tetraazacyclododecane-1,4,7-trisacetic Finally, we applied UV-Ag/TiO 2 -HCOOH together with DTNB derivatization to the determination of Cd-induced PCs in P. tricornutum. 28,29 Typical chromatograms obtained are shown in Fig. 3.…”
mentioning
confidence: 99%